Challenges of SME exporting ; a case study of a halal food manufacturer - Ahamat, Amiruddin; Jaafar, Adib Akram; Shah Wahid, Mansor; Robani, Anidah; Ismail, Albert Feisal @ Muhd Feisal; Aris, Amir (2023)
Muslim food demand increased by 3.1% in 2019 from 1.13 trillion to 1.17 trillion, then dropped in 2020 before increasing by 3.5% CAGR over five years to 1.38 trillion in 2024. Even though Malaysia has the most extensive halal ecosystem in the world, it only makes up a small part of the world's export value. As of 2020, Malaysia is the 19th largest exporter in the world. The purpose of this article is to examine the challenges of small and medium enterprises (SME) producing and exporting halal foods. This study makes use of exploratory research to assess the challenges of SME in this domain. An in-depth individual interview with an expert was done and the selection criteria of the participant was based on the SME involved in halal export. Jalen Sdn Bhd was the selected SME entity in this research topic. The interview's concepts, themes, and patterns were investigated using thematic analysis, while extracting the codes, the Nvivo 12 Pro software was used. The primary outcome of this study is assess the challenges of SME producing and exporting halal food: difficulty of acquiring halal-certified raw material and obtaining Good Manufacturing Practise (GMP) and Hazard Analysis Critical Control Point (HACCP) certification. By recognizing these challenges will help SME looking for solutions. Hence, SMEs in Malaysia can maximise export volume, produce more revenue, and close the economic gap, all of which help make Malaysia a sustainable economy.